A Generic Method to Monitor Completeness and Speed of Medical Documentation Processes - Dugas, M.; Dugas-Breit, S. (Methods of Information in Medicine, 2012)
Background: Physicians dedicate approximately a quarter of daily work to documentation. Completeness and speed of medical documentation processes are important parameters, because they can affect quality of healthcare.Objectives: A generic method to monitor these quality parameters is proposed and its utility is demonstrated in two examples.Methods: Based on a generic event-driven process chain of a medical documentation process, completeness functions for created and finalized documents (available versus required documents by time) are defined. The 95%-quantile of process time is applied as performance indicator of documentation speed. A plotting function for these parameters is provided: completeness and speed of medical documentation (CSMD)-plot. Open source code and a sample data set are available in the Supplement.Results: This methodology is applied to analyze the effect of an electronic dictation system on discharge letter documents. CSMD-plot detects significant differences regarding speed and completeness of the process before and after implementation of electronic dictation; in addition, it pinpoints differences regarding these quality parameters in documentation processes between different clinical departments. In a second example, CSMD-plot is used to analyze follow-up documentation of a clinical trial. Due to its generic design, CSMD-plots can be applied to other medical documentation processes such as order-entry processes.Conclusions: Monitoring of completeness and speed of medical documentation is feasible and can provide quantitative information on these processes.
Keywords: Medical documentation process; completeness; electronic dictation system; CRF; clinical trial documentation